Interactions between a Small Bubble and a Greater Solid Particle during the Flotation Process. (2nd November 2019) - Basařová, Pavlína; Zawala, Jan; Zedníková, Mária
ABSTRACT: The interaction between bubbles and solid particles is an important mechanism in many industrial processes and flotation is a significant component of the most utilized applications. While flotation of mineral ores deals with fine particles and larger bubbles, the aim of this review is to focus on the opposite case; the interaction between smaller bubbles and larger particles encountered mostly in plastic flotation. Plastic flotation seems to be one of the appropriate methods for separating plastics, which is necessitated by increasing plastic consumption and the growing need to recycle. The first part of the article focuses on the problem of the collision of a bubble with a particle, both spherical and planar. The collision efficiency is discussed. The second part is devoted to the problem of liquid film rupture and the creation of the three-phase contact line. The third and final part focuses on the problem of the three-phase line expansion and the effect of surfactants on the resulting bubble stability.